PENGEMBANGAN MEDIA INFOGRAFIS DIGITAL INTEGRATIF PAI-IPAS UNTUK MI MUHAMMADIYAH SAINS QUR’AN PONOROGO - Dwi Widiastuti; Ismail (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to design and analyze the effectiveness of integrative digital infographic media combining Islamic Education (PAI) and science in enhancing students’ understanding of religious and scientific concepts, as well as instilling Islamic values at MI Muhammadiyah Sains Qur’an Ponorogo. The research employs a qualitative descriptive approach using observation, interviews, and documentation methods. The results indicate that the digital infographic media, designed according to students’ characteristics—including high religiosity, interest in science, and critical thinking ability—can present material interactively, link scientific concepts with Qur’anic verses, and encourage reflection on Islamic values. The implementation of this media improves conceptual understanding, facilitates learning of abstract science topics, and nurtures Islamic character that is creative, critical, and responsible. In conclusion, integrative PAI-science digital infographic media is effective as a holistic learning tool that combines faith, knowledge, and morals, and is relevant to the needs of modern education.